Nanostructured hybrid films containing nanophosphor: Fabrication and electronic spectral properties - Camacho, Sabrina Alessio [UNESP]; Aoki, P. H. B. [UNESP]; Constantino, C. J. L. [UNESP]; Aroca, R. F.; Pires, A. M. [UNESP] (Elsevier B.V. Sa, 2012)
The intensive research of the optical properties of rare-earth ions is due to the high quantum efficiency of their emission, very narrow bands, and excellent fluorescence monochromaticity. The photoluminescence data presented here show that the nanophosphor remains a green emitter in Layer-by-Layer (LbL) films leading to potential application in optical devices or biological labeling. The LbL technique, an established method for thin film fabrication with molecular architecture control, is used in the manufacture of a hybrid film containing the cationic polyelectrolyte poly (allylamine hydrochloride) (PAH) and Y2O3: Er, Yb nanophosphor. The spectroscopic properties of this luminescent nanomaterial are extracted from the spectral data of the powder, cast film and LbL films. The growth of the LbL film was monitored by absorbance versus concentration plots in ultraviolet-visible (UV-Vis) absorption spectroscopy. The presence of both PAH and nanophosphor in the LbL film was confirmed by Fourier transform infrared (FTIR) absorption spectroscopy. The FTIR data also ruled out the existence of chemical interactions between the PAH and nanophosphor layers, which means that secondary interactions (like Van der Waals forces) might be the driving forces for LbL film growth. The morphology and the spatial distribution of the LbL film components along the film surface were probed with micrometer spatial resolution combining optical microscopy and Raman mapping. In addition, the observation of intense electronic emission lines from doping ions showed micro-spectroscopy as a highly sensitive analytical technique for characterization of films containing nanophosphors. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: LbL films; Nanophosphor; Photoluminescence; Raman